Respuesta :
Answer:
x=-2
Step-by-step explanation:
-4x – 6(3x + 4) = -4 + 8(1 - x)
Distribute
-4x – 18x -24 = -4 + 8 -8x
Combine like terms
-22x -24 = 4-8x
Add 22x to each side
-22x+22x -24 = 4-8x+22x
-24 =4+14x
Subtract 4 from each side
-24-4 = 4+14x-4
-28 = 14x
Divide each side by 14
-28/14 =14/14
-2 =x
Answer:
x = -2
Step-by-step explanation:
-4x – 6(3x + 4) = -4 + 8(1 - x)
combine like terms
-22x - 24 = -4 + 8 - 8x
Move the variable to the left-hand side and change the sign
-22 + 8 x - 24 =4
-14x = 4 + 24
-14x = 28
Divide both sides of the equation by -14
x = -2